2017
DOI: 10.1002/agr.21514
|View full text |Cite
|
Sign up to set email alerts
|

International aggregate agricultural supply for grain and oilseed: The effects of efficiency and technological change

Abstract: This paper analyses the effects of the main determinants of international aggregate agricultural supply. We propose a new model that captures the farmers' expectations through the storage approach, instead of using Nerlove's basic model. As an innovation, we add the effects of efficiency and technological change directly, thus achieving a more powerful and informative estimation than with the usual dynamic model. Moreover, we consider the effect of climate and construct a sowing and harvesting calendar for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…We confirm previous findings in terms of a negative relationship between arbitrage and grain price volatility: in particular, storage acts as an authentic buffer of volatility in grain market (Guerra et al 2014;Ott 2014;Tadesse et al 2014;Clech and Fillat-Castejón 2017). We found that trade flows influence price volatility of grain, as shown by Ivanic and Martin (2014).…”
Section: Discussionsupporting
confidence: 91%
“…We confirm previous findings in terms of a negative relationship between arbitrage and grain price volatility: in particular, storage acts as an authentic buffer of volatility in grain market (Guerra et al 2014;Ott 2014;Tadesse et al 2014;Clech and Fillat-Castejón 2017). We found that trade flows influence price volatility of grain, as shown by Ivanic and Martin (2014).…”
Section: Discussionsupporting
confidence: 91%
“…This means that natural resource abundance is a key factor in pushing the LAC TFP toward the technology frontier. This effect can be explained by the technological boom registered in agriculture during the last two decades (Le Clech and Fillat-Castejón 2020) and its importance in the world agricultural supply (Le Clech and Fillat-Castejón 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of in situ added value processing facilities usually improves farmers' rentability, as Sanders, Altman & Ferraro (2014) evaluated the impact of soybean processing yields and the adoption of new technologies. Moreover, Le Clech & Fillat-Castejón (2017) concluded that farmer's innovation and development are the most important aspects in the formation of commodities and derivatives prices. Therefore, the economic feasibility of adding a soy protein products production plant to a typical extrusion processing plant needs to be analyzed, since it could provide valuable information for the productive development of the central rural region of Argentina (Accoroni, 2015).…”
Section: Introductionmentioning
confidence: 99%